HAWA: SI WANITA PERTAMA (EVE: THE FIRST WOMAN) - Milton T. Pardosi (Fakultas Filsafat Universitas Advent Indonesia, 2015)
Eve was the first woman who lived on this earth. She is the wife of Adamand created by God from Adam’s rib. In the life of Eve, especially before sin, shehad advantages that may never be owned by every woman who has ever lived on thisearth. But those advantages disappeared for she believed the words of Satan (Snake)rather than the word of God. The issue discussed in this paper is what the advantagesthat Eve had not shared by other women? Another thing is to discuss what thecauses of the fall of Eve into sin?The purpose of this paper is to evaluate the life of Eve before sin with theadvantages that she has and the reasons why she fell into sin. There are severallessons to be drawn from the life of Eve. At least she has ten special advantages.There are lessons, too, that can be drawn from either the cause of the fall of Eve andalso solutions for her. Those lessons are, first, do not let this life be alone without afriend. Second, do not walk to the place where there is temptation in it.Furthermore, do not argue with the temptation. Fourth, do not add or take away theWord of God. Next, do not give even a slightest attention to the devil or temptation.Sixth, do not make other people falls into sin. Seventh, all actions have a definiterisk. Finally, remain always to have hope although has fallen into sin.